1962
DOI: 10.1111/j.1748-1716.1962.tb02498.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Effects on Lumbo‐Sacral Internewones Activated by Somatic Afferents

Abstract: LUNDBERG, A., U. NORRSELL and P. VOORHOEVE. Pyramidal effects on lurnbo-sacral interneurones activated by somatic afferents. Acta physiol. scand. 1962. 56. 220-229. -Intracellular recording was made from 23 interneurones in the dorsal horn and intermediate region. Stimulation of the sensorimotor cortex evoked excitatory postsynaptic potentials in interneurones receiving excitatory action from: 1) group I muscle afferents, 2) flexor reflex afferents, 3) cu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1967
1967
2006
2006

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…The pyramidal effects on interneurones were studied by and Lundberg, Norrsell & Voorhoeve (1962). They found that electrical stimulation of the post cruciate cortex facilitated the segmental interneurones.…”
Section: Discussionmentioning
confidence: 99%
“…The pyramidal effects on interneurones were studied by and Lundberg, Norrsell & Voorhoeve (1962). They found that electrical stimulation of the post cruciate cortex facilitated the segmental interneurones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rubrospinal and corticospinal tracts facilitate FRA pathways (Hongo et al, 1969(Hongo et al, , 1972Hultborn et al, 1976;Jankowska et al, 1976;Lundberg and Vooehoeve, 1962) so that these tracts can produce fine movements (see Jankowska, 1992). Signals from the midbrain locomotor region also excite group II interneurons (Edgley et al, 1988;Schefchyk et al, 1990) and induce rhythmic firing of reciprocal Ia interneurons (Carol and Jordan, 1987;Feldman and Orlovsky, 1975) and…”
Section: (3) Interaction Between the Reticulospinal System And Fra Symentioning
confidence: 99%
“…Activity in the latter two pathways facilitates transmission in reflex paths to motoneurones and primary afferents by giving excitatory action to their interneurones Lundberg, Norrsell & Voorhoeve, 1962;Hongo, Jankowska & Lundberg, 1965;Lundberg, 1964Lundberg, , 1967. However, in many interneurones IPSPs are evoked from the two pathways, in fact much more frequently than from the dorsal reticulospinal system.…”
mentioning
confidence: 99%